NILAI DAN PRINSIP PENDIDIKAN ISLAM MULTIKULTURAL - Lalu Muhammad Iqbal (An-Nahdlah: Jurnal Pendidikan Islam, 2025)
This study aims to examine the values and principles of multicultural Islamic education as an effort to create harmony in diverse societies. Multicultural Islamic education integrates Islamic values with respect for cultural, linguistic, and belief diversity. This study focuses on key values such as tolerance, justice, equality, and respect for differences, as well as the principles underpinning the practice of Islamic education in a multicultural context, including inclusivity, dialogue, and collaboration. The research adopts a qualitative approach using literature review methods, referencing works by Islamic scholars and multicultural education theories. The findings reveal that multicultural Islamic education is deeply rooted in the theological foundations of the Qur'an and Hadith, emphasizing the importance of ukhuwah (brotherhood), unity in diversity, and the recognition of human rights. Implementing these values and principles strengthens intergroup relations and reduces potential social conflicts. The study concludes that multicultural Islamic education is not only relevant but also an urgent necessity in addressing the challenges of globalization, which often triggers identity tensions. By applying these values and principles, educational institutions can contribute to building an inclusive, just, and harmonious society.